A carbene stabilized precursor for the spatial atomic layer deposition of copper thin films. Issue 89 (16th October 2020) - Boysen, Nils; Misimi, Bujamin; Muriqi, Arbresha; Wree, Jan-Lucas; Hasselmann, Tim; Rogalla, Detlef; Haeger, Tobias; Theirich, Detlef; Nolan, Michael; Riedl, Thomas; Devi, Anjana
Abstract : This is the first report on a plasma enhanced spatial atomic layer deposition (APP-ALD) process at atmospheric pressure to grow conducting metallic Cu thin films from a carbene stabilized precursor. Abstract : This paper demonstrates a carbene stabilized precursor [Cu( t Bu NHC)(hmds)] with suitable volatility, reactivity and thermal stability, that enables the spatial plasma-enhanced atomic layer deposition (APP-ALD) of copper thin films at atmospheric pressure. The resulting conductive and pure copper layers were thoroughly analysed and a comparison of precursor and process with the previously reported silver analogue [Ag( t Bu NHC)(hmds)] revealed interesting similarities and notable differences in precursor chemistry and growth characteristics. This first report of APP-ALD grown copper layers is an important starting point for high throughput, low-cost manufacturing of copper films for nano- and optoelectronic devices.